The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.29121/ijetmr.v8.i4.2021.905
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Implementation of Lean Construction Techniques in Gujarat Construction Industry

Abstract: Lean construction technique has been arisen from endeavouring and applying Japanese lean manufacturing philosophy to the construction industry. Large research is being done recently and an ongoing process to adopt lean principles to the construction industry to enhance the efficacy, amelioration of waste. The success of the lean technique is evident, but some major reports indicated that major challenges are related to the Mis-conceptualisation of lean thinking, and some case studies have ascertained that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The literature includes numerous studies about barriers that face the adoption of lean construction [3,21,28,34,55,59,60,[63][64][65][66][67][68][69][70][71][72][73][74][75][76]. However, there is no study about this topic in Jordan.…”
Section: Methodsmentioning
confidence: 99%
“…The literature includes numerous studies about barriers that face the adoption of lean construction [3,21,28,34,55,59,60,[63][64][65][66][67][68][69][70][71][72][73][74][75][76]. However, there is no study about this topic in Jordan.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the authors identi ied the projects which would have performed better if BIM was implemented. In the interviews, it was discovered that the Gujarat construction industry has a lack of knowledge of modern technologies and consuming more time in the design stage (Thakkar and Shah (2021). Furthermore, in construction tenure, some projects had involved some extra cost due to the mistakes in drawings.…”
Section: Methodsmentioning
confidence: 99%
“…A study that evaluated LC practices for enhancing safety in the Gaza Strip revealed several obstacles, including a lack of understanding of the LC concept, a lack of government support for implementing novel techniques in construction projects and a lack of understanding of how to use LC techniques for enhancing safety (Enshassi et al , 2021). Resistance to change and culture, inappropriate design detail and procedure, cultural and human attitudinal challenges, a lack of coordination and communication and a lack of target value design were some significant obstacles to the introduction of LC techniques in Gujarat’s construction industry (Thakkar and Shah, 2021). In a similar study conducted on the construction projects in Peru to investigate the barriers to LC implementation, it was discovered that the biggest obstacles to the successful implementation of LC were a lack of government policies, a lack of partnerships between the academy and organizations and high consumption of time and resources with no payoff (Huaman-Orosco and Erazo-Rondinel, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%